The awareness of reading and listening proficiency through a toefl practice to measure strengths and weaknesses in the receptive skills in third year Students of the Modern Languages Major at the Department of Foreign languages, University of El Salvador, year 2015 - Flores de Pérez, Ana Ruth
Standardized tests help students to measure their real proficiency. Based on this, the following research main objective is to reveal how the implementation of standardized test could help students and teachers to have a reliable system to know students’ English academic proficiency. In addition, this research looks for demonstrating how the lack of standardized test implementation in Modern Languages Major impedes the students to know their real English proficiency level in their receptive skills. Modern Languages is a major whose purpose is to make students learn other languages and use them with expertise. Consequently, it is really important for the students to know their proficiency and improvement when learning a foreign language, since nowadays; it is required to have a certificate to show one’s performance and work as a teacher or in other professional areas. In the course of this research, skills were evaluated through the standard test TOEFL and the use of The ACTFL Proficiency Guidelines in order to help students to know their real English proficiency and subsequently they could decide the best strategies to improve in their weak areas and continue strengthening their successes. Standardized tests are not being put into practice in most English foreign language majors; therefore, the importance of this work is to show out how important it is to implement this kind of standardized test to help students to not only know and be aware about their real English skills but also to prepare them for their professional life. Implementing this type of test will address students into their strengths and weaknesses in the receptive English skills and based on this knowledge, they will have the opportunity to make decisions about their learning process. Finally, this research also sought to verify if the lack of a standardized test impeded the students’ knowledge of their English proficiency. This work helped the researchers to know how interested students were to get informed about their English proficiency, strengths and weaknesses in their receptive skills.